Play-fairway analysis for geothermal resources and exploration risk in the Modoc Plateau region. (September 2017) - Siler, Drew L.; Zhang, Yingqi; Spycher, Nicolas F.; Dobson, Patrick F.; McClain, James S.; Gasperikova, Erika; Zierenberg, Robert A.; Schiffman, Peter; Ferguson, Colin; Fowler, Andrew; Cantwell, Carolyn
Highlights: Play-fairway exploration in the Modoc Plateau region revels new geothermal prospects. Bonham Ranch, NV, New Pine Creek, CA/OR, Eagle Lake, CA, Vya, NV, and Boulder Flat, NV are favorable prospects with relatively low exploration risk. Bonham Ranch, NV, New Pine Creek, CA/OR, Boulder Flat, NV and Vya, NV are Basin and Range-type. Eagle Lake, CA is Cascade arc-type. Abstract: The region surrounding the Modoc Plateau, encompassing parts of northeastern California, southern Oregon, and northwestern Nevada, lies at an intersection between two tectonic provinces; the Basin and Range province and the Cascade volcanic arc. Both of these provinces have substantial geothermal resource base and resource potential. Geothermal systems with evidence of magmatic heat, associated with Cascade arc magmatism, typify the western side of the region. Systems on the eastern side of the region appear to be fault controlled with heat derived from high crustal heat flow, both of which are typical of the Basin and Range. As it has the potential to host Cascade arc-type geothermal resources, Basin and Range-type geothermal resources, and/or resources with characteristics of both provinces, and because there is relatively little current development, the Modoc Plateau region represents an intriguing potential for undiscovered geothermal resources. It remains unclear however, what specific set(s) of characteristics are diagnostic of Modoc-type geothermal systems and how or if those characteristics are distinct from Basin and Range-type or Cascade arc-type geothermal systems. In order to evaluate the potential for undiscovered geothermal resources in the Modoc area, we integrate a wide variety of existing data in order to evaluate geothermal resource potential and exploration risk utilizing 'play-fairway' analysis. We consider that the requisite parameters for hydrothermal circulation are: 1) heat that is sufficient to drive circulation, and 2) permeability that is sufficient to allow for fluid circulation in the subsurface. We synthesize data that indicate the extent and distribution of these parameters throughout the Modoc region. 'Fuzzy logic' is used to incorporate expert opinion into the utility of each dataset as an indicator of either heat or permeability, and thus geothermal favorability. The results identify several geothermal prospects, areas that are highly favorable for the occurrence of both heat and permeability. These are also areas where there is sufficient data coverage, quality, and consistency that the exploration risk is relatively low. These unknown, undeveloped, and under-developed prospects are well-suited for continued exploration efforts. The results also indicate to what degree the two 'play-types, ' i.e. Cascade arc-type or Basin and Range-type, apply to each of the geothermal prospects, a useful guide in exploration efforts.